Instant Degradation of Organic Dyes in Contaminated Rivers Using Iron-Doped Zinc Quaternary-Based Quantum Dots Nanocatalyst - Nande Mgedle; Oluwatobi Samuel Oluwafemi (Reactions)
Organic dyes such as methylene blue (MB) and rhodamine 6G (Rh 6G), when dissolved in water, pose a serious threat to the environment, humans, and aquatic life. In this study, we report the synthesis of Fe-doped ZnCuInS/ZnS core/shell quantum dots (FeZCIS/ZnS QDs) in aqueous solution by varying the iron concentrations (0%, 1%, 3%, 5%, 7%, and 10%) for the instant removal of these organic pollutants in contaminated water. The as-synthesized FeZCIS/ZnS QDs were negatively charged and spherical in shape with a diameter of 2.97 nm ± 0.73 nm. Furthermore, it showed improved quantum yield (QYs) compared to the undoped with an average lifetime of 37.15 ns (3% Fe-doped QDs). The undoped ZCIS/ZnS QDs showed percentage removal efficiency of 94.42% and 93.97% for MB and Rh 6G in contaminated deionized water, respectively, and 90.73% (MB) and 1.28% (Rh 6G), respectively, in contaminated rivers. However, the 3% FeZCIS/ZnS QDs showed a percentage removal efficiency of 99.94% and 95.79% for MB and Rh 6G in contaminated deionized water, respectively, and 91.42% and 11.11%, respectively, in rivers contaminated with the dyes. Increasing the concentration of the nanocatalyst to 4 mg/mL improved the removal efficiency of Rh 6G in contaminated rivers to 93.28% and 94.40% using ZCIS/ZnS QDs and FeZCIS/ZnS QDs, respectively.